The effect of parenting in the digital era on the behaviour of elementary school students - Minsih; Aisyah Nur’Aini (Universitas Pendidikan Ganesha, 2022)
Departing from the negative impacts caused by digital media, the term digital parenting emerged as an effort to minimize its negative impacts. The reason for carrying out this research is because of the many facts that many have not implemented digital parenting. The purpose of this study is to analyses whether there is an effect of digital parenting on behaviour. The method used in this research is descriptive quantitative with a simple linear regression data analysis technique. The participant of this involving parents totaling (n=75) and being respondents. The data collection method is using Google form questionnaire which was distributed through the WhatsApp group as an intermediary for the homeroom teacher. The technique for data analysis that is used is regression line analysis. There are three results from this study: first, the influence of digital parenting on behaviour, digital parenting variable has a contribution effect on student behaviour variables. Second, most of the digital parenting patterns have been implemented, starting from supervision, restrictions, giving responses, and positive evaluations of parents on digital devices. Third, Student behaviour shows positive impact after digital parenting is implemented. So it can be concluded that it turns out that digital parenting influences student behaviour.